ANALISIS KINERJA PELAYANAN PERIZINAN BERUSAHA ONLINE MELALUI LAYANAN KONSULTASI DAN PENDAMPINGAN TERPADU SECARA ELEKTRONIK (LAKON-E PANDU) DI PROVINSI JAWA TENGAH - Elsa Putri Kusuma Wardani; Puji Astuti (Journal of Politic and Government Studies, 2026)
Digital transformation in public services encourages the development of electronic-based licensing services to improve efficiency, transparency, and service quality. LAKON-E PANDU is presented as an innovative online licensing consultation and assistance service to help business actors understand the risk based licensing mechanism through the OSS system. This study aims to assess the performance of this service in supporting optimal public services. The study used a qualitative method with a descriptive approach. Informants came from agencies and service users selected by purposive sampling based on business scale. Data were collected through interviews, documentation, and literature studies, then analyzed through reduction, presentation, and drawing conclusions with reference to e-service theory. The results of the study indicate that the performance of LAKON-E PANDU is generally quite optimal, in terms of efficiency, fulfillment, system availability, and privacy, although technical obstacles remain. Therefore, increased socialization, strengthening of the monitoring and evaluation system, stability of digital infrastructure, effectiveness of consultation services, and protection of user data are needed.